Property on the Line: Life on the Frontier between Copyright and the Public Domain - Austin, Graeme W (Victoria University of Wellington Law Review, 2013)
This article is an edited transcript of Professor Graeme W Austin's Inaugural Lecture, delivered in the Council Chamber of Victoria University of Wellington on 15 November 2012. Professor Austin was appointed Chair in Private Law in the Faculty of Law in November 2010. This lecture explores claims that in copyright law, the public domain is necessarily in opposition to proprietary rights, and suggests that in many contexts the incentives offered by copyright contribute to the vibrancy and volume of material that is available for downstream creativity and innovation. Drawing on his earlier work on the relationship between human rights law and intellectual property, Professor Austin's lecture advances the idea that cognisance of the human rights dimensions of intellectual property, including creators' human rights, should inform our understanding of the appropriate scope of the rights of copyright owners. The lecture concludes with a warning against the "Walmartization" of copyright.